(untitled) (Journal of the College of Basic Education, 2023)
The displacement of Ethiopian Jews (the Falasha) is one of the fruits that produced the Israeli-Ethiopian alliance. Israel has employed religious and historical factors, as well as political and intelligence methods, economic pressures, arms deals and international relations in order to pass this migration. The Falasha displacement operations took place in three stages (Musa - Sheba - Suleiman) during the eighties until 1991 and resulted in the displacement of more than thirty thousand Ethiopian Jews to Israel, and the United States of America contributed with its political weight to completing this deal under pressure from Jewish groups and the United States of America and Europe